Adapting a Traumatic Brain Injury Goals-of-Care Decision Aid for Critically Ill Patients to Intracerebral Hemorrhage and Hemispheric Acute Ischemic Stroke. (9th March 2021) - Goostrey, Kelsey J.; Lee, Christopher; Jones, Kelsey; Quinn, Thomas; Moskowitz, Jesse; Pach, Jolanta J.; Knies, Andrea K.; Shutter, Lori; Goldberg, Robert; Mazor, Kathleen M.; Hwang, David Y.; Muehlschlegel, Susanne
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Families in the neurologic ICU urgently request goals-of-care decision support and shared decision-making tools. We recently developed a goals-of-care decision aid for surrogates of critically ill traumatic brain injury patients using a systematic development process adherent to the International Patient Decision Aid Standards. To widen its applicability, we adapted this decision aid to critically ill patients with intracerebral hemorrhage and large hemispheric acute ischemic stroke. Design: Prospective observational study. Setting: Two academic neurologic ICUs. Subjects: Twenty family members of patients in the neurologic ICU were recruited from July 2018 to October 2018. Interventions: None. Measurements and Main Results: We reviewed the existing critically ill traumatic brain injury patients decision aid for content and changed: 1) the essential background information, 2) disease-specific terminology to "hemorrhagic stroke" and "ischemic stroke", and 3) disease-specific prognosis tailored to individual patients. We conducted acceptability and usability testing using validated scales. All three decision aids contain information from validated, disease-specific outcome prediction models, as recommended by international decision aid standards, including careful emphasis on their uncertainty. We replaced the individualizable icon arrays graphically depicting probabilities of a traumatic brain injury patient's prognosis with icon arrays visualizing intracerebral hemorrhage and hemispheric acute ischemic stroke prognostic probabilities using high-quality disease-specific data. We selected the Intracerebral Hemorrhage Score with validated 12-month outcomes, and for hemispheric acute ischemic stroke, the 12-month outcomes from landmark hemicraniectomy trials. Twenty family members participated in acceptability and usability testing ( n = 11 for the intracerebral hemorrhage decision aid; n = 9 for the acute ischemic stroke decision aid). Median usage time was 22 minutes (interquartile range, 16–26 min). Usability was excellent (median System Usability Scale = 84/100 [interquartile range, 61–93; with > 68 indicating good usability]); 89% of participants graded the decision aid content as good or excellent, and greater than or equal to 90% rated it favorably for information amount, balance, and comprehensibility. Conclusions: We successfully adapted goals-of-care decision aids for use in surrogates of critically ill patients with intracerebral hemorrhage and hemispheric acute ischemic stroke and found excellent usability and acceptability. A feasibility trial using these decision aids is currently ongoing to further validate their acceptability and test their feasibility for use in busy neurologic ICUs.